Persistence and dissipation pattern of captafol and metalaxyl residues on musk melon (Cucumis melo) fruits for safety constants - AWASTHI, M D; AHUJA, A K (The Indian Journal of Agricultural Sciences, 2013)
Â Â Â The foliar fungicide applications of captafol and mctalaxy1 carried out on musk melon (Cucumis melo L.) vines during fruiting stage of the crop in a supervised field trial showed the persistence of their residues for 10-15 days. The residues of captafol and metalaxy1 were analysed periodically after the last application through gas liquid charomatography. While captafol residues were retained on fruiit peel, metalaxyl resideues were repidly absorbed in the fruit pulp. Based on the persistence pattern of their residues, captafol treatment required waiting periods 4-8 days and metalaxy1 for 11-15 days for the residues to reduce to safe levels. The peeling off fruit feel could reduce the waiting period marginally for metalaxy1 due to the presence of residues in fruit pulp but captafol residues were removed with fruit peel for safe consumption of the fruits.